Identification of Barriers to Access Endovascular Treatment for Acute Ischemic Stroke in the Health Care System of Mexico: Results From a National Survey Among Endovascular Neurologists - Gongora-Rivera, Fernando; Gonzalez-Aquines, Alejandro; Marquez-Romero, Juan Manuel; , Neurological Endovascular Therapy – Mexican Group (NET-MX Group) (Frontiers in Neurology, 2021)
Background. Endovascular treatment (EVT) access for acute ischemic stroke (AIS) is the main challenge in Latin America. The Mexican Endovascular Reperfusion Registry (MERR) and the RESILIENT trial demonstrated the feasibility of EVT of AIS in Latin America, however, the MERR uncovered potential challenges to deliver EVT to AIS patients. Aim. To identify the perceived barriers to access EVT for AIS in a Latin American developing country. Methods. We surveyed endovascular neurologists in Mexico. The survey addressed the situation of thrombectomy in the country and the infrastructure and resources available in the participants’ practice institutions. The questionnaire inquired costs, barriers, and challenges to accessing EVT for AIS, emphasizing the prices and availability of medical devices needed for EVT. Results. We analyzed data from 15 participants. The most extreme identified barriers to access EVT were the lack of health coverage for EVT by the National Health System, the cost of the medical supplies for EVT, and inadequate knowledge of stroke symptoms in the general population. The median cost for EVT was USD 20,000 (IQR 7,500–20,000). From this amount, 60% (IQR 50-70%) corresponded to the medical devices' costs. EVT carried additional out-of-pocket costs in 90% of the hospitals and in 57% the costs exceed USD 10,000. Conclusion. Efforts at all government levels and society are required to tackle these barriers. An increase and efficient use of public funding for EVT coverage, deployment of continuous and targeted stroke education campaigns would be translated into a reduction in the inequities in EVT access in Mexico.